CONCENTRATION OF WHEY BY USING MEMBRANES FOR DIET BEVERAGES - Fikri Haikhal, Mochamad
Whey is a wastewater from cheese production that can be further processed into a high-protein diet drink. This diet drink is expected to overcome the problem of obesity in Indonesia which has almost doubled, from 19.1% in 2007 to 35.4% in 2018. Whey based products that are suitable for diet drinks are Whey Protein Concentrate (WPC). The conventional WPC production process uses an ultrafiltration and diafiltration membrane, followed by a concentration process by evaporation and spray drying. Conventional processing may result in rancidity due to retained fat and whey protein denaturation due to evaporation at a temperature of 70oC. Alternative processing that can be done is pretreatment to remove fat content and whey concentration using membrane distillation (MD). Concentration using MD is carried out at a lower temperature than the evaporation process so that it can produce concentrated whey with better quality. The purpose of this experiment is to determine the pretreatment method and the MD, namely Direct Contact Membrane Distillation (DCMD) or Osmotic Membrane Distillation (OMD), which is best used for the process of concentrating whey into Whey Protein Concentrate (WPC) for diet drinks. Whey obtained from the Mozzarella Cheese Production House – Ganesha Sora in Lembang, West Java. The variation of the pretreatment methods are thermocalcic precipitation and pH correction, followed by microfiltration (MF). The variation of the concentration method are Direct Contact Membrane Distillation (DCMD) or Osmotic Membrane Distillation (OMD). Based on the experimental results, the best pretreatment variation is the thermocalcic precipitation. This variation resulted MF permeate with the lowest protein rejection of 12,51% and removed all fat content in whey. The best concentration process was the OMD with a final protein content of 67.56 grams/L. The product is potentially suitable for diet drinks because it has fairly high protein content. Based on the products on the market, ready-to-go diet drink products require around 7-8 grams of protein for a 200 mL serving. Diet drink products with a protein content of 7-8 grams can be produced using 125 mL of the resulting WPC product, then flavorings and other necessary ingredients can be added.